Auger electron angular distributions following excitation or ionization from the Xe 3d and F 1s levels in xenon difluoride. Issue 3 (24th December 2021) - Forbes, Ruaridh; Hockett, Paul; Powis, Ivan; Bozek, John D.; Pratt, Stephen T.; Holland, David M. P.
Abstract : Electron spectroscopy following Xe 3d and F 1s ionization in XeF2 elucidates the influence of core electrons on molecular bonding. Abstract : Linearly polarized synchrotron radiation has been used to record polarization dependent, non-resonant Auger electron spectra of XeF2, encompassing the bands due to the xenon M45 N1 N45, M45 N23 N45, M45 N45 N45 and M45 N45 V and fluorine KVV transitions. Resonantly excited Auger spectra have been measured at photon energies coinciding with the Xe 3d5/2 → σ* and the overlapped Xe 3d3/2 /F 1s → σ* excitations in XeF2 . The non-resonant and resonantly excited spectra have enabled the Auger electron angular distributions, as characterized by the β A parameter, to be determined for the M45 N45 N45 transitions. In the photon energy range over which the Auger electron angular distributions were measured, theoretical results indicate that transitions into the ε f continuum channel dominate the Xe 3d photoionization in XeF2 . In this limit, the theoretical value of the atomic alignment parameter ( A 20 ) characterizing the core ionized state becomes constant. This theoretical value has been used to obtain the Auger electron intrinsic anisotropy parameters ( α 2 ) from the β A parameters extracted from our non-resonant Auger spectra. For a particular Auger transition, the electron kinetic energy measured in the resonantly excited spectrum is higher than that in the directly ionized spectrum, due to the screening provided by the electron promoted into the σ* orbital. The interpretation of the F KVV Auger band in XeF2 has been discussed in relation to previously published one-site populations of the doubly charged ions (XeF2 2+ ). The experimental results show that the ionization energies of the doubly charged states predominantly populated in the decay of a vacancy in the F 1s orbital in XeF2 tend to be higher than those populated in the decay of a vacancy in the Xe 4d level in XeF2 .